Response of Groundnut (Arachis hypogaea L.) to Lime and Different Levels of Sulphur - Aier, Imnatemjen; Nongmaithem, D. (International Journal of Bio-resource and Stress Management, 2021)
A field experiment was conducted in the Experimental Research Farm of School of Agricultural Sciences and Rural Development (SASRD), Nagaland University during the kharif season 2018. Groundnut variety ICGS-76 was sown @ 70 kg ha-1 for 60×20 cm2 spacing. The experiment was laid in split plot design with three replications. The main plot treatments consisted of two lime levels: lime @ 0 t ha-1 and lime @ 3 t ha-1 while the sub- plot treatments consisted of five sulphur levels: sulphur @ (0 kg ha-1, 10 kg ha-1, 20 kg ha-1, 30 kg ha-1 and 40 kg ha-1 along with recommended dose of fertilizer at 20:60:40 kg N, P2O5 and K2O ha-1 respectively in the form of diammonium phosphate and murate of potash. The results showed that application of lime @ 3 t ha-1 gave higher growth and yield attributes compared to no lime and also application of sulphur @ 40 kg ha-1 gave higher growth and yield attributes compared to lower doses of sulphur though there was only slight increase in the attributes between each successive doses of sulphur. Overall application of lime and sulphur increased all the yield attributes of groundnut, where the highest number of pods plant-1, seeds pod-1, 100 kernels weight, pod yield, kernel yield and stover yield were recorded when treatment was done with lime @ 3 t ha1 and sulphur @ 40 kg ha-1.